Hank The Cowdog: The Mopwater Files - Book 28 - Erickson, John R. (Houston TX : Gulf Publishing Co, 1997)
Summary: Hank the Cowdog, head of ranch security, discovers that drinking a bucket of plant food restores his energy, leading to a series of near-disasters.
Keywords: Dogs -- Fiction